Responsabilidad social empresarial y gestión administrativa - operativa en la empresa turística Aqua Expeditions S.A.C. año 2022 - Marapara Vasquez, Rivaldo Ronald (2023)
The central objective of the study was to analyze corporate social responsibility and administrative-operative management in the tourist company Aqua Expeditions S.A.C. – 2022, for this the variables were analyzed separately and their statistical relationship was determined, the study was of a quantitative, descriptive and relational non-experimental design with a population of 98 employees of the company, using a questionnaire as a collection instrument. of 24 questions, with an ordinal measurement scale with a statistical reliability in Cronbach's alpha of 0.917; The work concluded in relation to company social responsibility acceptable to 85% of participants considering aspects such as business policy, labor regulations, care for the environment and community relations, identifying positive aspects in each of them with a small margin of collaborators. who consider these should improve and that 90% consider that the operational administrative management is positive taking into account aspects of planning, business organization, management and control of luxury tourist services, the study identifies that there is a considerable positive relationship between the responsibility business social and operational administrative management with a significance of 0.000 and a Spearman's Rho of 0.654.